Prophylactic effects of magnesium and vitamin E in rat spinal cord radiation damage: evaluation based on lipid peroxidation levels - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
This study investigated the neuroprotective effects of magnesium sulfate prophylaxis and vitamin E prophylaxis in a rat model of spinal cord radiation injury. Groups were subjected to different treatment conditions for 5 days prior to irradiation, and outcomes were evaluated on the basis of lipid peroxidation levels in cord tissue. Four groups of rats were investigated: no radiation/treatment (n = 4), intraperitoneal (i.p.) saline 1 ml/day (n = 6), i.p. vitamin E 100 mg/kg/day (n = 6), and i.p. magnesium sulfate 600 mg/kg/day (n = 6). The thoracic cord of each non-control rat was exposed to 20 Gy radiation in a LINAC system using 6 MV x-rays, and malondialdehyde (MDA) levels (reflecting lipid peroxidation level) were determined 24 hours post-irradiation. The MDA levels in thoracic cord segments from the control rats were used to determine baseline lipid peroxidation. The mean levels in the control, saline-only, vitamin E, and magnesium sulfate groups were 12.12 +/- 0.63, 27.0 +/- 2.81, 17.71 +/- 0.44, and 14.40 +/- 0.47 nmol/mg tissue, respectively. The MDA levels in the saline-only group were significantly higher than baseline, and the levels in the vitamin E group were significantly lower than those in the saline group (P < 0.05 for both). The levels in the magnesium sulfate group were dramatically lower than those in the saline group (P < 0.001). The results indicate that i.p. magnesium sulfate has a marked neuroprotective effect against radiation-induced oxidative stress in the rat spinal cord. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: lipid peroxidation; magnesium; myelopathy; prophylaxis; radiation; spinal cord; vitamin E; GAMMA-RADIATION; X-RAYS; INJURY; HYPOMAGNESEMIA; SULFATE; RADIOPROTECTION; DEFICIENCY; TRAUMA; MOUSE; LIVER